Going the Distance: Field Approaches to Researching the Rural – A Research Note - Shukla, Rashi K.; Inglis, Melissa (International Journal of Rural Criminology, 2023)
Studies of crime in rural settings have expanded in recent years. Seldom discussed are the challenges associated with conducting rural field research. This research note describes the methodological approaches utilized in a multi-year study of rural law enforcement across Oklahoma and a nearby state in the United States. Research aims and methodology evolved over time in line with the flexibility inherent within ethnographic approaches. Interviews and field visits were conducted with 39 individuals from 2017 to 2019 for the purpose of understanding rural communities, crime and policing. Data were gathered through in-depth interviews, field visits, ride-alongs, observations and photographs. Owing to the nature of the subject matter, researchers had to maintain flexibility throughout the research process. This research note discusses the range of approaches utilized to gather data, obstacles encountered and insights discovered through the process.